2022
DOI: 10.1101/2022.05.06.490941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Working Memory performance based on specific individual EEG spatiotemporal features

Abstract: Working Memory (WM) is a limited capacity system for storing and processing information, which varies from subject to subject. Several works show the ability to predict the performance of WM with machine learning (ML) methods, and although good prediction results are obtained in these works, ignoring the intersubject variability and the temporal and spatial characterization in a WM task to improve the prediction in each subject. In this paper, we take advantage of the spectral properties of WM to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The article claimed that there were no existing methods for predicting working memory ability. Another study in 2022 predicted a working memory performance based on the spatio-temporal features [11]. The result indicated that the spatial and temporal characteristics emerged during the working memory process, and that the working memory performance can be predicted using regularized linear discriminant analysis (RLDA).…”
Section: Introductionmentioning
confidence: 99%
“…The article claimed that there were no existing methods for predicting working memory ability. Another study in 2022 predicted a working memory performance based on the spatio-temporal features [11]. The result indicated that the spatial and temporal characteristics emerged during the working memory process, and that the working memory performance can be predicted using regularized linear discriminant analysis (RLDA).…”
Section: Introductionmentioning
confidence: 99%